Case Report: 60-Year-Old Female with Ischemic Stroke, Type 2 Diabetes Mellitus, and Hypertension - Husnawati, Husnawati; Andriani, Dita Maulida; Rizki, Famella Yustika; Wanty, Fitri Prima; Sinaga, Giacinta Gracesandy; Rahmi, Helvy; Anggraini, Laurentin Leni; Khairani, Putri; Sakinah, Rezkila; Rasihen, Sri Lidya; Wahyudi, Wahyudi; Sinulinga, Yori Yunita (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Ischemic stroke remains a leading cause of death and disability worldwide, with increasing incidence each year. Patients with comorbidities, such as Type 2 diabetes mellitus (DM), pose additional treatment challenges due to a higher risk of drug-related problems (DRPs), particularly drug interactions. Objective: This study aims to describe pharmaceutical care in female patients diagnosed with ischemic stroke and Type 2 DM, with a focus on identifying and evaluating DRPs. Method: A descriptive case study was conducted. Data were collected through medical records and patient monitoring, focusing on the identification and analysis of potential DRPs in the context of pharmaceutical care. Results: The study found drug interactions as the most prominent DRP. An interaction between potassium slow-release (KSR) and candesartan was identified as requiring monitoring. Additionally, moderate interactions were found between atorvastatin and clopidogrel, as well as atorvastatin and amlodipine. These interactions have the potential to influence therapeutic outcomes. Conclusion: The prescribed medication regimen was generally appropriate for the patient's condition. Nevertheless, the presence of DRPs highlights the importance of regular monitoring and dose adjustments. Optimizing pharmaceutical care through early detection and management of DRPs is essential to ensure treatment safety and effectiveness in patients with complex conditions.